The international monetary system and the less developed countries - Bird, Graham R. (London : Macmillan, 1978)
This book investigates the relationship between the international monetary system and the less developed countries of the world. In the period since 1945 growing concern has been shown over the international monetary problems which LDCs have been significant participants in the reform of the international monetary system.
Includes index.
Bibliography: p. 319-337.
usc 30/10/18
Loans
Keywords: International finance; Foreign exchange rates; Finance; Foreign exchange rates; Economic development; Developing countries